2012
DOI: 10.1155/2012/326506
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Programme for Person-Centred Learning and Support Designed for Preschool Children with Long-Term Illness: A Pilot Study of a New Intervention

Abstract: For children living with long-term illness, school age is a risk period with regard to psychosocial ill health and poor compliance with treatment. There is a need for methods to promote health, well-being, and self-esteem. This study describes a new concept for supporting children, person-centred web-based learning and support, which has been tested in 12 preschool children and incorporates learning about feelings, relationships, and the right to integrity. SKYPE was used for conversations between the child an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The child's narrative was the acknowledgement that the child had learned, but also the confirmation of the feeling of being a partner. Preschool children are not always used to talking with other unknown adults and they often need time to learn to know each other, as is shown in an earlier study reported by our group (Hellstrom et al, 2012).…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…The child's narrative was the acknowledgement that the child had learned, but also the confirmation of the feeling of being a partner. Preschool children are not always used to talking with other unknown adults and they often need time to learn to know each other, as is shown in an earlier study reported by our group (Hellstrom et al, 2012).…”
Section: Discussionmentioning
confidence: 54%
“…The child may not be used to communicating experiences in words and therefore posture, gestures and facial expressions are important for achieving a full understanding of the narrative and the person. Communicating via SKYPE allowed the use of images, facilitating understanding (Jenholt Hellstrom et al, 2012;Simeonsdotter Svensson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Skype technology has been shown to be useful in web-based support for children who are unable to read and write and makes the child feel comfortable as they can participate from their own home (Hellström, Simeonsdotter Svensson, Pramling Samuelsson, & Jenholt Nolbris, 2012;Simeonsdotter Svensson, Pramling Samuelsson, Hellström, & Jenholt Nolbris, 2013). The current study was undertaken to investigate support in daily life to young children using a web-based programme.…”
Section: Introductionmentioning
confidence: 99%